Does ESG investment reduce carbon emissions in China? - Cong, Yingnan; Zhu, Chen; Hou, Yufei; Tian, Shuairu; Cai, Xiaojing (Frontiers in Environmental Science, 2022)
This study explores the relationship between ESG investments and carbon emissions in China. Our results show that 1% increase in environmental investments would cause 0.246% decrease in CO2 emissions and 0.558% decrease in carbon emission intensity. The impact of ESG investment is heterogeneous across the developed and underdeveloped regions. Environmental investments in the advanced eastern region have significantly improved carbon productivity. In contrast, environmental investments in the central and western regions significantly reduced carbon emissions, but they have little impact on carbon productivity.